Transcriptomic Analysis of the Effect of GAT-2 Deficiency on Differentiation of Mice Naïve T Cells Into Th1 Cells In Vitro - Ding, Xueyan; Chang, Yajie; Wang, Siquan; Yan, Dong; Yao, Jiakui; Zhu, Guoqiang (Frontiers in Immunology, 2021)
The neurotransmitter γ-aminobutyric acid (GABA) is known to affect the activation and function of immune cells. This study investigated the role of GABA transporter (GAT)-2 in the differentiation of type 1 helper T (Th1) cells. Naïve CD4+ T cells isolated from splenocytes of GAT-2 knockout (KO) and wild-type (WT) mice were cultured; Th1 cell differentiation was induced and transcriptome and bioinformatics analyses were carried out. We found that GAT-2 deficiency promoted the differentiation of naïve T cells into Th1 cells. RNA sequencing revealed 2984 differentially expressed genes including 1616 that were up-regulated and 1368 that were down-regulated in GAT-2 KO cells compared to WT cells, which were associated with 950 enriched Gene Ontology terms and 33 enriched Kyoto Encyclopedia of Genes and Genomes pathways. Notably, 4 signal transduction pathways (hypoxia-inducible factor [HIF]-1, Hippo, phospholipase D, and Janus kinase [JAK]/signal transducer and activator of transcription [STAT]) and one metabolic pathway (glycolysis/gluconeogenesis) were significantly enriched by GAT-2 deficiency, suggesting that these pathways mediate the effect of GABA on T cell differentiation. Our results provide evidence for the immunomodulatory function of GABA signaling in T cell-mediated immunity and can guide future studies on the etiology and management of autoimmune diseases.